Perfectionism and attitudes towards doping in athletes: the mediating role of achievement goal orientations. Issue 3 (4th May 2022) - Hardwick, Benjamin; Madigan, Daniel J.; Hill, Andrew P.; Kumar, Simon; Chan, Derwin K. C.
ABSTRACT: Perfectionism predicts attitudes towards doping in athletes. It is currently unclear, however, why this is the case. To help shed light on this particular issue, in the present study we provided a first examination of whether achievement goal orientations explain (mediate) the relationship between perfectionism and attitudes towards doping. A sample of 173 athletes (mean age 24.4 years) completed measures of perfectionistic strivings, perfectionistic concerns, ego-orientation, task-orientation, and attitudes towards doping. Based on bias-corrected bootstrapping of indirect effects, ego-orientation mediated the positive relationships between perfectionistic strivings and attitudes towards doping and perfectionistic concerns and attitudes towards doping. Task-orientation mediated the negative relationship between perfectionistic strivings and attitudes towards doping. In this regard, athletes high in either dimension of perfectionism have more favourable attitudes because of a tendency to define success as outperforming others. However, those athletes high in perfectionistic strivings may simultaneously hold less favourable attitudes because they also have a tendency to define success as improving their own performance.